Physico-chemical changes during growth and maturation of tangerine fruit cv. 'Sai Nam Phueng' and 'See Thong' - Worawaran Roongruangsri (2018)
Several tangerine cultivars are popular and commercially produced in Thailand. Despite this, no published data exists on the physico-chemical characteristics of the Thai cultivars, assessing their quality, throughout the various stages of fruit development. This study will assess the quality of the physicochemical characteristics of two cultivars, 'Sai Nam Phueng' and 'See Thong', during growth and maturation. Chlorophyll degradation and carotenoid accumulation in peel resulted in changing color from green to yellow-orange throughout fruit development of both cultivars. Carotenoid accumulation in juice resulted in changing color from yellow-orange to deep orange. Titratable acidity (TA) and citric acid content of both cultivars peaked at the early growth stage, then rapidly decreased during growth and slightly decreased during maturation. Malic acid and vitamin C content were very high at early growth stage, and then declined toward fruit maturation. Isocitric acid content gradually decreased during maturation. The total soluble solids (TSS), TSS/TA ratio, sucrose, glucose and fructose content rapidly increased during growth and slowly increased during maturation. During maturation, 'Sai Nam Phueng' had higher TA, TSS, citric acid, vitamin C, sucrose, glucose and fructose content and lower peel carotenoid, isocitric acid content, juice pH and TSS/TA ratio than 'See Thong'. Peel and juice colors, peel chlorophyll, juice carotenoid and malic acid content did not differ between the two cultivars during maturation.